Z ROZWAŻAŃ NAD ZAGADNIENIAMI CZASOPRZESTRZENI W POWIEŚCI MICHAIŁA BUŁHAKOWA MISTRZ I MAŁGORZATA - Chudzińska-Parkosadze, Anna (Acta Neophilologica, 2013)
The article is devoted to the problem of time and space as the essential factors of the world model created in The Master and Margarita, the famous novel written by Mikhail Bulgakov. As many critics has already noticed, there are three basic space dimensions in the considering work of prose – Jerusalem, Moscow and the mysterious world of Woland. As the matter of fact the core problem of research concerns the latter. The world from which Woland is coming is presented as a kind of inter-world between the other two, on the one hand, and as the objective Universe embracing them, creating in this way the unity of three dimensions, on the other hand. Moreover, in this piece of work, there has been made an attempt to recode the Woland’s world by analysing the motifs of it through the symbols and themes of gnosis.